1998
DOI: 10.1029/97ja01785
|View full text |Cite
|
Sign up to set email alerts
|

Ion dynamics in magnetic reconnection: Comparison between numerical simulation and Geotail observations

Abstract: Abstract.We study the plasma thermMization and acceleration process in collisionless magnetic reconnection by using a two-dimensional, particle-in-cell numericM simulation and discuss the plasma mixing process of cold lobe ions into the plasma sheet. We find that the plasma thermalization timescale is longer than the dynamic timescale of magnetic reconnection and that non-Maxwellian ion velocity distribution functions produced during the evolution of magnetic reconnection play an important role on the dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 36 publications
12
141
0
Order By: Relevance
“…Imada et al (2007) showed how the supra-thermal electrons appeared associated with another B z transient around 09:48:50 UT, which could well be explained by acceleration of bounced population at the front of the outward flow region as predicted by Hoshino et al (1998) in PIC simulations. Large-amplitude (up to 50 mV/m) solitary waves, identified as electron holes, were seen near the outer edge of the plasma sheet, within and on the edge of a density cavity, at distances on the order of a few ion inertial lengths from the center of the current sheet between 09:47 and 09:51 UT .…”
Section: Event 2: Interpretation With Nenl Modelmentioning
confidence: 95%
“…Imada et al (2007) showed how the supra-thermal electrons appeared associated with another B z transient around 09:48:50 UT, which could well be explained by acceleration of bounced population at the front of the outward flow region as predicted by Hoshino et al (1998) in PIC simulations. Large-amplitude (up to 50 mV/m) solitary waves, identified as electron holes, were seen near the outer edge of the plasma sheet, within and on the edge of a density cavity, at distances on the order of a few ion inertial lengths from the center of the current sheet between 09:47 and 09:51 UT .…”
Section: Event 2: Interpretation With Nenl Modelmentioning
confidence: 95%
“…Meanwhile, the particle gains energy from its motion along the electric field E y . However, the acceleration process cannot go infinitely, because the particle will finally become magnetized and be guided by the B z component to be ejected out in the x direction with fast speed [Speiser, 1967;Hoshino et al, 1998]. The net motion of ions in the dawn-dusk direction then carries the current.…”
Section: 1002/2014gl060440mentioning
confidence: 99%
“…Since we found that some of the non-gyrotropic ions observed by Geotail can be understood as the behavior of magnetic reconnection region, we think that the above non-Maxwellian electrons are observed in the thin plasma sheet during magnetic reconnection. It is also known that the thickness of the plasma sheet becomes of the order of ion skin depth during magnetic reconnection from the kinetic simulation study (e.g., Hoshino et al, 1998;Hesse et al, 1999;Shay et al, 1999).…”
Section: Geotail Observationmentioning
confidence: 99%
“…Based on the recent satellite observations and the kinetic simulation studies of reconnection, it is revealed that the thickness of the plasma sheet near the X-type region becomes of the order of ion skin depth (e.g., Hoshino et al, 1998;Hesse et al, 1999;Shay et al, 1999). Since the kinetic features beyond the MHD description appears in the macroscopic scale length, the self-consistent understanding of both the macroscopic evolution of reconnection and the microscopic behavior of plasma dynamics becomes important.…”
Section: Introductionmentioning
confidence: 99%